Mental Health Status in Patients with Fibromyalgia - Sousan Kolahi,; Ali Fakhari,; Mehrzad Hajaliloo,; Alireza Khabbazi,; Sahar Hassanzadeh Dizaj,; Mahdi Hemati, (Journal of Basic & Applied Sciences, 2014)
Background: It has long been shown that chronic conditions are usually accompanied by psychosocial disorders. Fibromyalgia (FM) is not an exception in this regard. The aim of this study is to evaluate the mental health in FM patients. Methods: In an analytic-descriptive setting, patients with diagnosis of FM were inquired according to general health questionnaire-28 (GHQ-28) and severity of pain was inquired based on visual analogue scale (VAS). Somatic symptoms, anxiety/insomnia, social dysfunction and severe depression were assessed. Results: One hundred female patients with mean age of 44.66±11.34 years were enrolled. According to GHQ-28, 55% of the patients with FM have suffered from psychological abnormalities.The prevalence of suspected psychological disorders, were 68 % in ""somatic symptoms"", 18% in “depression” and ""anxiety and insomnia"" and 53% in ""social dysfunction"". There were a significant positive correlation between VAS and level of somatic symptoms, social dysfunction and severe depression. Conclusion: This study showed that a considerable portion of patients with FM may suffer concurrently from psychological disorders. The probability of these diseases increases with the severity of pain, hence effective pain reducing policies may be useful in providing a better quality of life.